Development economics and structuralist macroeconomics essays in honor of Lance Taylor - Dutt, Amitava Krishna; Ros, Jaime; Edward Elgar Publishing (Cheltenham ; Northampton, Mass. : Edward Elgar, 2003)
Lance Taylor is widely considered to be one of the pre-eminent development economists in the world and is known for his work on development planning, macroeconomics of development, stabilization policy, and the global economy. He has also been the major force behind structuralist economics, which is seen by many to be a major alternative to orthodox development economics and policy prescriptions. The essays in this volume, written by well-known scholars in their own right, make contributions to each of these areas while honoring the contributions made by Lance Taylor.
pt. 1. Introduction -- pt. 2. Approaches to development and planning -- pt. 3. Finance and asset markets -- pt. 4. Stabilization, adjustment and growth -- pt. 5. Beyond neo-liberalism : the firm, industrial policy and competitiveness -- pt. 6. The north, the south and globalization.
Includes bibliographical references and index.
Keywords: Development economics; Finance -- Developing countries; Developing countries -- Economic policy; Economic stabilization -- Developing countries; Globalization -- Economic aspects; Macroeconomics; Electronic books